2022
DOI: 10.3389/fmolb.2022.1001941
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of bempedoic acid treatment in polycystic kidney disease cells and mice

Abstract: ADPKD has few therapeutic options. Tolvaptan slows disease but has side effects limiting its tolerability. Bempedoic acid (BA), an ATP citrate-lyase (ACLY) inhibitor FDA-approved for hypercholesterolemia, catalyzes a key step in fatty acid/sterol synthesis important for cell proliferation. BA is activated by very long-chain acyl-CoA synthetase (FATP2) expressed primarily in kidney and liver. BA also activates AMPK. We hypothesized that BA could be a novel ADPKD therapy by inhibiting cyst growth, proliferation,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Bempedoic acid (BA) antagonizes the ATP citrate-lyase (ACLY) enzyme upstream of HMGCoA reductase and is approved as an adjunct to diet and statin therapy in familial hypercholesterolemic patients who require additional lowering of LDL-C Ruscica et al, 2022). In animal models BA also activates AMPK (Pinkosky et al, 2016;Hallows et al, 2022) and reduces cystic growth, TKW and BUN (Hallows et al, 2022). BA seems to have a reduced risk of muscle-related side effects reported with statins (Ruscica et al, 2022) although a recent meta-analysis concluded that statins cause a small risk of muscle symptoms that are outweighed by the known cardiovascular benefits of statins (Cholesterol Treatment Trialists' Collaboration, 2022).…”
Section: Bempedoic Acidmentioning
confidence: 99%
“…Bempedoic acid (BA) antagonizes the ATP citrate-lyase (ACLY) enzyme upstream of HMGCoA reductase and is approved as an adjunct to diet and statin therapy in familial hypercholesterolemic patients who require additional lowering of LDL-C Ruscica et al, 2022). In animal models BA also activates AMPK (Pinkosky et al, 2016;Hallows et al, 2022) and reduces cystic growth, TKW and BUN (Hallows et al, 2022). BA seems to have a reduced risk of muscle-related side effects reported with statins (Ruscica et al, 2022) although a recent meta-analysis concluded that statins cause a small risk of muscle symptoms that are outweighed by the known cardiovascular benefits of statins (Cholesterol Treatment Trialists' Collaboration, 2022).…”
Section: Bempedoic Acidmentioning
confidence: 99%
“…Bempedoic acid (BA) antagonizes the ATP citrate-lyase (ACLY) enzyme upstream of HMGCoA reductase and is approved as an adjunct to diet and statin therapy in familial hypercholesterolemic patients who require additional lowering of LDL-C ( Huynh, 2019 ; Ruscica et al, 2022 ). In animal models BA also activates AMPK ( Pinkosky et al, 2016 ; Hallows et al, 2022 ) and reduces cystic growth, TKW and BUN ( Hallows et al, 2022 ). BA seems to have a reduced risk of muscle-related side effects reported with statins ( Ruscica et al, 2022 ) although a recent meta-analysis concluded that statins cause a small risk of muscle symptoms that are outweighed by the known cardiovascular benefits of statins ( Cholesterol Treatment Trialists' Collaboration, 2022 ).…”
Section: Cholesterol Reducing Agentsmentioning
confidence: 99%